Quiet Engagement with the Taliban. Issue 5 (3rd September 2021) - Strand, Arne; Suhrke, Astri
Abstract: The international response to the Taliban's sudden assumption of power in Kabul will make a critical difference for future developments in the country. Among the range of choices, a strong case can be made for engagement, dialogue and assistance. Immediate humanitarian need and widespread extreme poverty warrant substantial aid, including funds to maintain basic programmes established over the past two decades in health and education. The experience of international organisations working in Afghanistan during Taliban rule in the late 1990s constitutes a constructive precedent. Cooperation over aid is also an opening for a dialogue in which wider concerns can be aired. As in the late 1990s, sanctions and international isolation are likely to prove counterproductive by harming the Afghan people and strengthening the hardline factions of the Taliban.